Actual Issues of Development of Small Business Entities (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article today, the development of small business and private entrepreneurship, the expansion of the scale of production in enterprises and thereby ensuring the employment of the population, obtaining high income, as well as the wide attraction of foreign investment funds, and at the same time achieving effective economic growth through the support of entrepreneurial activities by the state the paths are illuminated. In addition, a scientific proposal and practical recommendations have been developed for the establishment of production activities with the rational use of available resources.